Representations of the First Places of Learning on the Paintings of the Medieval Serbian Monasteries - Dragomir S. Sando (University of Belgrade, Teacher Education Faculty, 2019)
The iconography created during the 800-year-long Serbian history depicts the times filled with important historical and cultural events. The frescoes reflect the development of diverse trends in our educational system. The walls of various monasteries depict the lives of the saints and the real events occurring during their life time. Everyday objects used in the medieval Serbia, such as furniture, writing materials, medical instruments, decorations, the attire of the kings, patrons, monks, etc., illustrate the culture of the day. The aim of the paper is to explore the originality, pedagogical propedeutics, and the beginnings of Serbian education, which was manifested, didactically speaking, in the apparent teaching - this fact is evident in the frescoes and icons of the monasteries and temples. The frescoes, icons and biblical scenes are works of art, but their function is primarily sacral, as well as instructive. The image of a saint on the wall precisely reflected the environment of the saint's life and the message (motto) of his life. The messages conveyed in the frescoes primarily point to the works and wonders of Christ, emphasise the importance of mercy to the other, good deeds that had to be practised, and piety (piety in a sense of living according to God's rules). The method used in the paper is the biblical-iconographic approach, and the author also relied on the instructive elements represented in the lives of the saints and demonstrated in the personalities of the saints interpreted in an interdisciplinary way: from the artistic, technical-decorative, ecclesiastical-aesthetical, and historical perspectives.